PENGARUH MODEL TEAM GAMES TOURNAMENT (TGT) BERBANTUAN MEDIA WORDWALL TERHADAP HASIL BELAJAR IPS PESERTA DIDIK KELAS III DI SDN 03 SIMPANG HARU - Naldi Putra; Ade Irma Suryani; Riri Marfilinda (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was motivated by the low learning outcomes in Social Studies, the lack of student engagement, and the use of less varied and monotonous teaching models. These conditions have negatively affected the Social Studies learning outcomes of third-grade students at SDN 03 Simpang Haru. This study aims to determine the effect of the Teams Games Tournament (TGT) learning model assisted by Wordwall media on students' Social Studies learning outcomes. This research employed a quasi-experimental method with a Nonequivalent Posttest-Only Group Design. The population of this study consisted of all third-grade students at SDN 03 Simpang Haru. The sample included. Data were collected using a multiple-choice test consisting of 20 items. The results of the data analysis showed that the mean score of the experimental group was 87.50, which was higher than that of the control group, 72.80. Based on the statistical test results, the Asymp. Sig. (2-tailed) value was 0.001 < 0.05, indicating that H₀ was rejected and H₁ was accepted. Therefore, it can be concluded that there is a significant effect of the Teams Games Tournament (TGT) model assisted by Wordwall media on the Social Studies learning outcomes of third-grade students at SDN 03 Simpang Haru.